2021
DOI: 10.1109/lcomm.2020.3028375
|View full text |Cite
|
Sign up to set email alerts
|

FD-FBMC: A Solution for Multicarrier Full Duplex Cellular Systems

Abstract: This letter reports on a critical issue with the application of OFDM to a full-duplex (FD) cellular system. With small frequency offsets of uplink signals, the downlink BER increases considerably. This is attributed to the high spectral-leakage-interference from the OFDM waveforms of geographically nearby uplink users. As an alternative, we propose applying the FBMC waveform to the same FD cellular system scenario. We calculate the precise spectral-leakage-interference for OFDM and FBMC, based on which, we set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Compared to (15) which is for homogeneous QoS (identical target SINRs among UEs) case, the RSI term of kth uplink in (56) contains lth UE's target SINR and vice versa in (58). Therefore, unlike (15) and (17),…”
Section: F Effect Of Tx Power Constraintsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to (15) which is for homogeneous QoS (identical target SINRs among UEs) case, the RSI term of kth uplink in (56) contains lth UE's target SINR and vice versa in (58). Therefore, unlike (15) and (17),…”
Section: F Effect Of Tx Power Constraintsmentioning
confidence: 99%
“…In [14], TNFD and HD were compared when the BS is equipped with multiple antennas and it was demonstrated that the average sum rate of TNFD can be increased with the employment of linear precoding. Meanwhile, in the other works on OFD cellular system [6], [15], [16], the UEs as well as the BS are modelled to be equipped with FD transceivers, and they can bi-directionally communicate with the BS as shown in Fig. 1(b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…que agrupan los K pulsos encargados de transmitir cada k muestras del primer subsímbolo. Situando los K pulsos transmisores de las k muestras del segundo subsímbolo y así sucesivamente hasta tener M bloques de K pulsos transmisores [9,10]. Donde cada agrupación de K pulsos realiza la elevación en frecuencia correspondiente.…”
Section: Matriz De Transmisión Aunclassified
“…In [8], the performance of Full Duplex FBMC (FD-FBMC) was examined, considering it as a solution for the full-duplex multicarrier scheme for cellular systems. The performance of the OFDM system was reported in terms of spectral leakage interference.…”
Section: Introductionmentioning
confidence: 99%